High-efficient oil/water separation membrane based on MXene nanosheets by co-incorporation of APTES and amine functionalized carbon nanotubes. Issue 6 (December 2021) - Zhang, Lei; Wei, Ke; Zeng, Guangyong; Lin, Qingquan; Liu, Xiang; Chen, Yonggang; Sengupta, Arijit
Abstract: Membrane based separation technology has great prospects in the treatment of oily wastewater, which involves serious environmental and health concern. In the present investigation, 3-aminopropyltriethoxysilane (APTES) was used to modify MXene nanosheets and amine functionalized carbon nanotubes (ACNTs) was used to control the layer spacing of MXene followed by the fabrication of a series of APTES/MXene-ACNTs composite membranes supported on cellulose acetate (CA) by vacuum filtration. The surface morphology analysis by scanning electron microscope (SEM) and atomic force microscopy (AFM) revealed that, the composite membranes exhibited excellent hydrophilicity as well as high efficiency in oil/water emulsion separation. The rejection ratios of composite membranes for lubricating oil emulsion and vegetable oil emulsion were found to be more than 99%. Compared to the pure MXene membrane M1 (500.7 L·m −2 ·h −1 ·bar −1 ), the pure water flux of the best modified membrane APTES/MXene-ACNTs/CA (M4) reaches up to 2892.8 L·m −2 ·h −1 ·bar −1 . Moreover, the modified membrane shows good anti-fouling and anti-swelling characteristics even after several cyclic consecutive cycles. This work demonstrates a new horizon in the applications of two-dimensional membrane materials. Graphical Abstract: ga1 Highlights: APTES/MXene-ACNTs/CA composite membranes were fabricated successfully. The membranes exhibited high-efficient for O/W emulsion separation. The membranes showed good anti-fouling and anti-swelling properties.